Ideologies and Social Work : Historical and Contemporary Analyses; GSC002085, GSC002086 - Desai, Murli (Jaipur Rawat Publications, 2002)
With partial reference to India.
Includes bibliographical references (p. [213]-227) and index.
Keywords: Social Work - Education -- Social Work - Ideologies; Social Change - Western History -- Social Change - Indian History; Social Change - Contemporary Ideologies - Contemporary Analyses -- Social Work - Profession - History